2017
DOI: 10.1007/s12144-017-9715-4
|View full text |Cite
|
Sign up to set email alerts
|

Perpetrating Cyber Dating Abuse: A Brief Report on the Role of Aggression, Romantic Jealousy and Gender

Abstract: There is increasing evidence that the use of elec-tronic communication technology (ECT) is being integrated into romantic relationships, which can be used as a medium to control a romantic partner. Most research focuses on the vic-tims of cyber dating abuse, however, we focused on the factors that predict perpetration of cyber dating abuse. We explored whether aggression (verbal aggression, physical aggression, anger and hostility), romantic jealousy (emotional, cognitive and behavioral jealousy), and gender p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
2
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 46 publications
5
51
2
12
Order By: Relevance
“…Zweig et al (2013) found that female students were more often victims of cyber sexual abuse than male, but they were less often victims of non-sexual cyber abuse. In Deans and Bhogal's (2017) study, gender was significantly associated with CDA, with women reporting less perpetration of CDA than men, contrary to other previous studies (e.g., Bennett et al, 2011;Burke et al, 2011) were women were more likely than men to perpetrate controlling online behaviors. These inconsistent findings have been attributed to the fact that men and women perpetrated CDA differently: men tend to perpetrate more direct acts of aggression (Perry & Pauletti 2011;Taylor & Xia, 2018) while women more indirect acts (Hyde, 2005), such as monitoring behaviors (Taylor & Xia, 2018).…”
Section: Risk and Protective Factors Of Cyber Dating Abusecontrasting
confidence: 99%
“…Zweig et al (2013) found that female students were more often victims of cyber sexual abuse than male, but they were less often victims of non-sexual cyber abuse. In Deans and Bhogal's (2017) study, gender was significantly associated with CDA, with women reporting less perpetration of CDA than men, contrary to other previous studies (e.g., Bennett et al, 2011;Burke et al, 2011) were women were more likely than men to perpetrate controlling online behaviors. These inconsistent findings have been attributed to the fact that men and women perpetrated CDA differently: men tend to perpetrate more direct acts of aggression (Perry & Pauletti 2011;Taylor & Xia, 2018) while women more indirect acts (Hyde, 2005), such as monitoring behaviors (Taylor & Xia, 2018).…”
Section: Risk and Protective Factors Of Cyber Dating Abusecontrasting
confidence: 99%
“…These results show the importance of better understanding the risk factors that may be at the origin of these abusive behaviours. As an example, in an exploratory study involving 189 participants, Deans and Bhogal [ 58 ] found that some psychological factors, such as hostility and behavioural jealousy, explained CDA perpetration, thus highlighting the importance to understand the nature of these abusive behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Many other studies have analyzed the differences in implication depending on the participants' gender, but their results have provided mixed results. Some researchers indicate that men have higher perpetration rates [25], while others have found higher victimization rates for men [26]. Other studies contradict these results and state that women present higher perpetration [18,27] and victimization [27][28][29] rates, or have found no significant differences between genders [23].…”
Section: Risk Factors For Engaging In Dating Abusementioning
confidence: 98%